Remote sensing : models and methods for image processing - Schowengerdt, Robert A. (Academic Press, 2007)
"Remote Sensing, now in its 3rd edition, seamlessly connects the art and science of remote sensing with the latest interpretative tools and techniques of computer-aided image processing. Newly expanded and updated, this edition delivers more of the applied scientific theory and practical results that helped the previous editions earn wide acclaim, becoming classroom and industry standards. New book design provides superior image presentation of full color plates and improved readability."--Jacket